2006
DOI: 10.1042/bj20060426
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a signalling system that incorporates both redundancy and diversity:ArabidopsisSUMOylation

Abstract: The reversible post-translational modifier, SUMO (small ubiquitin-related modifier), modulates the activity of a diverse set of target proteins, resulting in important consequences to the cellular machinery. Conjugation machinery charges the processed SUMO so that it can be linked via an isopeptide bond to a target protein. The removal of SUMO moieties from conjugated proteins by isopeptidases regenerates pools of processed SUMOs and unmodified target proteins. The evolutionarily conserved SUMO-conjugating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 27 publications
3
94
0
Order By: Relevance
“…Recently, we reported the characterization of several SUMOs and ULPs from A. thaliana and demonstrated that ULP1 shows varying specificity for AtSUMO-1, -2, -3, and -5 as well as for M-SUMO-1, -2, and -4 and yeast SUMO (Smt3) (14). Sequence comparisons of these SUMOs and T-SUMO revealed a striking similarity (83% sequence identity) among AtSUMO-1, AtSUMO-2, and T-SUMO (supplemental Fig.…”
Section: Substrate Specificity Of Xopd-previous Results Showing Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported the characterization of several SUMOs and ULPs from A. thaliana and demonstrated that ULP1 shows varying specificity for AtSUMO-1, -2, -3, and -5 as well as for M-SUMO-1, -2, and -4 and yeast SUMO (Smt3) (14). Sequence comparisons of these SUMOs and T-SUMO revealed a striking similarity (83% sequence identity) among AtSUMO-1, AtSUMO-2, and T-SUMO (supplemental Fig.…”
Section: Substrate Specificity Of Xopd-previous Results Showing Thatmentioning
confidence: 99%
“…In Vitro Sumoylation Assays-In vitro sumoylation of 35 Slabeled mammalian HA-RanGAP with GST-AtSUMO-1, GSTAtSUMO-2, GST-AtSUMO-3, GST-AtSUMO-5, GST-T-SUMO, GST-Smt3, GST-M-SUMO-1, GST-M-SUMO-2, and GST-M-SUMO-4 was performed as described previously (14,25). In vitro peptidase assays using these sumoylated RanGAP proteins were performed as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a known drawback of bacterially expressed recombinant protein is the lack of eukaryotic post-translational modifications. In contrast, a variety of protein modifications have been described in RRL with examples that include phosphorylation, acetylation, glycosylation, ubiquitination, and isoprenylation (reviewed in 41 ) as well as sumoylation 42 and methylation. 43 The ability of RRL to REMSAs were performed with equimolar amounts of the in vitro translated proteins incubated with PHGPx SECIS RNA as described in Figure 3.…”
Section: Discussionmentioning
confidence: 99%